The regulatory effects of realgar and cinnabar on glucose metabolism in mice - Zhang, Yifan; Qu, Qingsong; Dai, Ertong; Liu, Ruiyan; Jin, Bilin; Lu, Zixuan; Kong, Hui; Zhang, Yue; Qu, Huihua; Zhao, Yan (Frontiers in Endocrinology, 2025)
BackgroundGlucose metabolism plays a central role in maintaining systemic energy homeostasis, and its dysregulation is closely linked to the pathogenesis of metabolic diseases such as diabetes mellitus. While traditional mineral medicines such as realgar and cinnabar have a long history of use, their roles in glycometabolism remain poorly defined.MethodsMale C57BL/6J mice were used to establish both normoglycemic and streptozotocin (STZ)-induced diabetic models. Oral glucose, starch, protein, fat, and cellulose load tests were performed to evaluate the effects of realgar and cinnabar on postprandial glycemia and thermoregulation. Random blood glucose, body temperature, and insulin levels were monitored. α-Glucosidase and α-amylase inhibition assays were conducted in vitro to explore potential digestive enzyme-targeted mechanisms.ResultsRealgar and cinnabar significantly reduced blood glucose levels in diabetic mice and attenuated postprandial glycemic excursions in normal mice following oral glucose and starch loading. Further analysis revealed elevated insulin levels and dose-dependent inhibition of α-glucosidase and α-amylase activities. However, these hypoglycemic effects were abolished when glucose was administered intraperitoneally, and no significant changes in blood glucose were observed under non-carbohydrate nutrient loads (fat, protein, or fiber).ConclusionThis study provides the first systematic evidence that realgar and cinnabar exert hypoglycemic effects, which involving enhanced insulin secretion and inhibition of key digestive enzymes. Their substrate-specific actions and partial influence on thermoregulation suggest broader roles in metabolic regulation and warrant further investigation in chronic models and energy homeostasis pathways.